2015
DOI: 10.3892/or.2015.3835
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA-17/20a suppresses cell proliferation in gastric cancer by modulating UBE2C expression

Abstract: microRNAs (miRNAs) are small non-coding RNAs that potentially play a critical role in carcinogenesis. Increasing evidence indicates that the miR-17/20 cluster is upregulated in numerous types of human cancers including gastric cancer which suggests that the miR-17/20 cluster may play an important role in tumorigenesis. However, its role in gastric cancer carcinogenesis remains poorly defined due to the lack of target gene information. The aim of the present study was to investigate the target genes of the miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Much effort has been spent on the study of the overexpression of UBE2C biological mechanisms in gastric cancer (29,30). This E2 protein catalyzes the ubiquitination and degradation of cyclins A and B, and acts together with the E3 ligase of the APC/C to participate in the regulation of the spindle assembly checkpoint (31).…”
Section: Discussionmentioning
confidence: 99%
“…Much effort has been spent on the study of the overexpression of UBE2C biological mechanisms in gastric cancer (29,30). This E2 protein catalyzes the ubiquitination and degradation of cyclins A and B, and acts together with the E3 ligase of the APC/C to participate in the regulation of the spindle assembly checkpoint (31).…”
Section: Discussionmentioning
confidence: 99%
“…miR‐545/374a, miR‐183/182, miR‐106b/25 and miR‐221/222 clusters (Zhao et al, ; Zhou et al, ; Li et al, ) all enhance cell proliferation. Conversely, miR‐1/133a, miR‐212/132, miR‐23b/27b, miR‐17/20 and miR‐302/367 clusters were downregulated in cancer, and act as inhibitors of cell proliferation (Hanieh, ; Mataki et al, ; Yang et al ., ; Zha ng et al ., ; Rice et al, ) Upregulation of oncogenic and downregulation of tumour‐suppressor miRNA clusters has been shown to upregulate expression of cyclin D2 ( CCND2 ), cyclin D1 ( CCND1) and wingless‐type MMTV integration site family, member 3A ( WNT3A) (Bonci et al, ; Di Leva et al, ; Lovat et al, ) and downregulate expression of anti‐proliferative genes such as PTEN, p21 , BIM and p27 (Wong et al, ; Zhu et al, ).…”
Section: Oncogenic and Tumour‐suppressor Mirna Clustersmentioning
confidence: 99%
“…Numerous studies have been performed on the role and related mechanism of miRNAs in numerous different kinds of diseases (9)(10)(11)(12). miRNAs bind primarily to the 3'-untranslated region (3'UTR) of their target messenger RNAs (mRNAs) to reduce their stability and decrease the expression of target mRNAs at the post-transcriptional level (13), which play important roles in various biological processes including cell growth, proliferation, differentiation and death (14)(15)(16)(17)(18)(19). Concerning chemotherapy in various types of cancers such as breast cancer, lung adenocarcinoma, glioblastoma, and ovarian cancer, recent studies have shown that miRNAs also act in important roles (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%